On the Homology Theory of Operator Algebras - Alaa Hassan Noreldeen (International Journal of Mathematics and Mathematical Sciences)
We investigate the cyclic homology and free resolution effect of a commutative unital Banach algebra. Using the free resolution operator, we define the relative cyclic homology of commutative Banach algebras. Lemmas and theorems of this investigation are studied and proved. Finally, the relation between cyclic homology and relative cyclic homology of Banach algebra is deduced.